Historical Examples in the Letters of Ivan IV to the Crimean Khanate and the Nogai Horde - M.V. Moiseev (Золотоордынское обозрение)
Objective: A study of the historical arguments of Ivan the Terrible in the context of diplomatic relations with the Tatar states. Research materials: A compilation of diplomatic letters of Tsar Ivan IV Vasilievich preserved in the books of ambassadorial records. Results and scientific novelty: The author used the whole compilation of the preserved diplomatic correspondence for the first time ever with the purpose of reconstructing a viewpoint of the Russian ruling elite. He established that the revision of the “Horde’s legacy” was started during the regency of Elena Glinskaya. By using real facts and precedents, while also allowing themselves at times to commit direct forgery, Moscow intellectuals created a picture of the past in which the Volga region belonged to the Russian princes even before the Mongol conquest. The fact that Tatar nobility engaged in swearing an oath to Moscow princes and later to the tsar played an important role in the system of argumentation employed by Muscovy. The author shows that the “Tmutarakan legend” of the origin of Astrakhan was used only inside the country and was necessary to convince the boyars on the necessity of its conquest. Choosing arguments, Russian diplomats relied on rhetorical formulas and images that were understandable within the Tatar cultural environment, and this led to the development of other ways of substantiating foreign policy claims which differed from those that were employed in European countries.